Development of monoclonal antibody and lateral test strip for sensitive detection of clenbuterol and related β2-agonists in urine samples. Issue 1 (2nd January 2016) - Khaemba, Gabriel Wafula; Tochi, Bitange Nipa; Mukunzi, Daniel; Joel, Isanga; Guo, Lingling; Suryobrobowo, Steven; Song, Shanshan; Kuang, Hua; Xu, Chuanlai
Abstract : Being the most used and preferred β2 -agonist, clenbuterol (CLB) has been reported to be illegally abused in animal production and breeding as it improves growth rate while inhibiting fat synthesis and deposition leading to buildup of lean muscle. Due to its potential hazard to human health, causing food poisoning that can be fatal, it has been forbidden as a growth promoter for food-producing animals in most countries including China. Therefore, frequent monitoring of CLB abuse is necessary for consumer safety against its residues. We therefore report development of a monoclonal antibody and lateral flow test strip for sensitive detection of CLB in urine samples. In this investigation, male BALB/C mice were first immunized for antibody production. Thereafter, gold nanoparticles were utilized for antigen and antibody immobilization during construction of the strip. Under optimized conditions, the cut-off limit of the test strip was found to be 2.5 and 5 ng/g in phosphate-buffered saline (PBS) and urine using the wet method. When the dry method was used for CLB detection, the cut-off limit of the test strip in PBS and urine was found to be 3 ng/g. Each test was evaluated within 6 min. The data obtained show that the strip developed is sensitive and has an advantage of fast test results and simplicity and hence can be adopted for screening of CLB residues in urine samples for mitigation of CLB residue effects to human health.